2018
DOI: 10.1007/s10943-018-0602-6
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Life Satisfaction: A Correlational Study of Undergraduate Students in Trinidad

Abstract: Religious behaviour tends to correlate positively with life satisfaction. The predictive power of this relationship is associated with various socio-demographic factors such as age, gender and religious affiliation. We investigated the relationship between religious involvement and life satisfaction in a multi-religious population of undergraduate medical students of the University of the West Indies. We used a cross-sectional design to assess 228 undergraduates (50 males and 178 females) on religiosity, relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 64 publications
2
14
1
Order By: Relevance
“…Regarding students' sense of belonging, males, females, and the minority gender groups did not differ significantly in their sense of belonging. Our findings are consistent with those by Habib (2018) who indicated that female and male college students did not have statistically significant differences in life satisfaction. However, our findings revealed that minority gender groups had significantly less satisfaction than males and females, and this might be due to the campus climate and the global climate that they have experienced.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding students' sense of belonging, males, females, and the minority gender groups did not differ significantly in their sense of belonging. Our findings are consistent with those by Habib (2018) who indicated that female and male college students did not have statistically significant differences in life satisfaction. However, our findings revealed that minority gender groups had significantly less satisfaction than males and females, and this might be due to the campus climate and the global climate that they have experienced.…”
Section: Discussionsupporting
confidence: 93%
“…Seniors reported significantly less satisfaction than freshmen or sophomores. Habib (2018) found that students from 19 to 21 reported significantly higher life satisfaction than those who were more than 28 years old. This is probably due to students' experience on campus.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In his study, Faisal (2016) highlighted that faith, an essential dimension of religion, contributes to developing "resilience" in adulthood. The results of our study differed with many studies that found a positive relationship between religiosity and life satisfaction, including the study Patel, Ramgoon & Paruk (2009) as well the study of Habib, Donald & Hutchinson (2018), which both found that women are more religious than men, religiosity is positively and significantly related to life satisfaction. As well, the study Okulicz-Kozaryn (2010) indicated that religious people tend to be extremists, meaning that they are either very satisfied with life or dissatisfied with life.…”
Section: Life Satisfaction and Religiositycontrasting
confidence: 99%
“…However, as Chukwuorji et al (2018) pointed out, religiosity, which is viewed as motivational in nature, cannot be omitted from mediators of well-being. Religious beliefs affect subjective well-being, with religious people mostly being happier than non-religious people, regardless of their faith (Berthold and Ruch 2014;Dolan et al 2008;Habib et al 2018). Moreover, results in a sample of UK adults demonstrated that intrinsic orientation and positive religious coping were significantly associated with higher psychological well-being that reflects human growth, positive functioning and existential life challenges (Lewis et al 2005).…”
Section: Personality Life Satisfaction and Religiositymentioning
confidence: 99%